2018
DOI: 10.1038/s41598-018-22354-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of quercetin in animal feed: effects on the P-gp expression and pharmacokinetics of orally administrated enrofloxacin in chicken

Abstract: Modulation of P-glycoprotein (P-gp, encoded by Mdr1) by xenobiotics plays central role in pharmacokinetics of various drugs. Quercetin has a potential to modulate P-gp in rodents, however, its effects on P-gp modulation in chicken are still unclear. Herein, study reports role of quercetin in modulation of P-gp expression and subsequent effects on the pharmacokinetics of enrofloxacin in broilers. Results show that P-gp expression was increased in a dose-dependent manner following exposure to quercetin in Caco-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The previously reported homology model of CXR [15] was used to dock a set of small molecules and evaluate their affinity to the binding site of the ligand binding domain. The docking scores and poses agreed with the previous results, and the binding energy of −7.8 kcal/mol suggested that berberine interacts favorably with CXR (Table 4, Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previously reported homology model of CXR [15] was used to dock a set of small molecules and evaluate their affinity to the binding site of the ligand binding domain. The docking scores and poses agreed with the previous results, and the binding energy of −7.8 kcal/mol suggested that berberine interacts favorably with CXR (Table 4, Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Homology modeling of CXR was performed following a previously described procedure [15]. The homology model for chicken P-glycoprotein (CP-gp) was produced as described previously [15], with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homology model of the cBCRP was generated using procedure described previously [ 35 ] with some modifications. Then, model availability was validated by comparing docking scores of known BCRP substrates and inhibitors into the efflux pump site.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking study showed that addition of flavonoid moiety not only provided several additional interactions but also did not disturb the binding mode of the quinolone . Therefore, covalently binding an antibiotic with an efflux pump inhibitor may probably develop antibiotics effective against resistant strains …”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%